Enhanced CAR T-cell engineering using non-viral Sleeping Beauty transposition from minicircle vectors - Monjezi, R.; Miskey, Csaba; Gogishvili, T.; Schleef, M.; Schmeer, M.; Einsele, H.; Ivics, Z.; Hudecek, Michael (Leukemia, 2017)
Immunotherapy with T cell modified with gamma-retroviral or lentiviral (LV) vectors to express a chimeric antigen receptor (CAR) has shown remarkable efficacy in clinical trials. However, the potential for insertional mutagenesis and genotoxicity of viral vectors is a safety concern, and their cost and regulatory demands a roadblock for rapid and broad clinical translation. Here, we demonstrate that CAR T cells can be engineered through non-viral Sleeping Beauty (SB) transposition of CAR genes from minimalistic DNA vectors called minicircles (MCs). We analyzed genomic distribution of SB and LV integrations and show that a significantly higher proportion of MC-derived CAR transposons compared with LV integrants had occurred outside of highly expressed and cancer-related genes into genomic safe harbor loci that are not expected to cause mutagenesis or genotoxicity. CD19-CAR T cells engineered with our enhanced SB approach conferred potent reactivity in vitro and eradicated lymphoma in a xenograft model in vivo. Intriguingly, electroporation of SB MCs is substantially more effective and less toxic compared with conventional plasmids, and enables cost-effective rapid preparation of therapeutic CAR T-cell doses. This approach sets a new standard in advanced cellular and gene therapy and will accelerate and increase the availability of CAR T-cell therapy to treat hematologic malignancies.
CRIS-Team Scopus Importer:2023-03-23